Tourism public policies: an analysis of Minas Gerais touristic circuits using cluster concept - Gomes, Bruno Martins Augusto; Silva, Valdir José da; Santos, Antônio Carlos dos (Revista Turismo em Análise, 2008)
In actual competitive economy the organizations that it composes your productive chain seek competitiveness. A form of the organizations acquire advantages competitive front to the market it is through the clusters. Noticing that tendency, the government of the state of Minas Gerais started to develop public politics of incentive to the regional articulation of the tourism. A bibliographical rising and a research with the directors and managers of the circuits were made. After analysis the collected data, it is ended that the Minas Gerais government's initiatives coincide with the cluster beginnings, however the circuits are still in implantation phase, hindering that that concept is totally implemented.